Efficacy of Antagonist Strains of Bacillus megaterium, Enterobacter cloacae, Pichia guilliermondii and Candida ethanolica against Bacterial Wilt Disease of Tomato - Ranamukhaarachchi1, David B. Hannaway2, Mai Thanh Nguyen1*, Senaratne L. (Journal of Phytology, 2011)
Bacterial wilt disease (BWD) caused by Ralstonia solanacearum is a serious and widespread disease in tomato. The persistence and its wide host range often restrict the effectiveness of cultural and chemical control measures. Four antagonists: Bacillus megaterium, Enterobacter cloacae, Pichia guillermondii and Candida ethanolica were tested and found significantly antagonistic to R. solanacearum in in vivo conditions with unsterilized soils and hence possess potential to control BWD in tomato. Enterobacter cloacae, Pichia guillermondii and Candida ethanolica also increased growth and fruit yield compared to the control. Disease severity varied with antagonist and time of application; compared with the control, disease severity was reduced 41.6-77.1% when antagonists were applied one week prior to transplanting tomato seedlings. These results can be used as a potential tool to control BWD in tomato commercially as an eco-friendly manner and provide encouragement for continued research on biological control of bacterial wilt disease by antagonists. Key words: Antagonists, Bacterial wilt, Bio-control, Ralstonia solanacearum, Soil-borne pathogen, Systemic disease, Tomato <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Mai Thanh Nguyen et al. Efficacy of Antagonist Strains of Bacillus megaterium, Enterobacter cloacae, Pichia guilliermondii and Candida ethanolica against Bacterial Wilt Disease of Tomato. J Phytol 3/2 (2011) 01-10